2013
DOI: 10.1159/000355732
|View full text |Cite
|
Sign up to set email alerts
|

Release From Glomerular Overload by the Addition of Low-dose Thiazide in Patients With Angiotensin Receptor Blocker-Resistant Hypertension

Abstract: Background/Aims: This multicenter, prospective, observational study assessed the renoprotective effects of losartan/thiazide combination therapy in terms of lowering the estimated glomerular filtration rate (eGFR). Methods: Adult patients with angiotensin receptor blocker (ARB)-resistant essential hypertension (n = 104) were enrolled and switched to combination therapy with losartan (50 mg/day) and hydrochlorothiazide (12.5 mg/day). Results: eGFR values declined significantly during the first 3 months, and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The effect of losartan in the change of intrarenal RAS: with Wistar rats in high-salt diet, Losartan failed to reduce SBP but abolished the increase of proteinuria, renal cortex renin, angiotensinogen, angiotensin II and urinary angiotensinogen when compared with high salt group [31]. There are similar accounts of the renal protective effect: the losartan/thiazide combination therapy attenuated glomerular overload, indicating that this therapy may provide glomerular protection in patients with an elevated GFR without causing prolonged damage to renal function [32]. With low-salt diet administering 50 mg Losartan inhibition of AT1 receptors could lead to activation of AT2 receptors, which maintain skin hyperaemia despite the increased level of vasoconstrictor thromboxane A2 [33].…”
Section: Introductionmentioning
confidence: 92%
“…The effect of losartan in the change of intrarenal RAS: with Wistar rats in high-salt diet, Losartan failed to reduce SBP but abolished the increase of proteinuria, renal cortex renin, angiotensinogen, angiotensin II and urinary angiotensinogen when compared with high salt group [31]. There are similar accounts of the renal protective effect: the losartan/thiazide combination therapy attenuated glomerular overload, indicating that this therapy may provide glomerular protection in patients with an elevated GFR without causing prolonged damage to renal function [32]. With low-salt diet administering 50 mg Losartan inhibition of AT1 receptors could lead to activation of AT2 receptors, which maintain skin hyperaemia despite the increased level of vasoconstrictor thromboxane A2 [33].…”
Section: Introductionmentioning
confidence: 92%
“…23,24 Several previous studies reported that they have not only an antihypertensive but also a urinary protein-decreasing effect. [25][26][27] Separately, add-on therapy of spironolactone to RAS inhibitors inhibits the aldosterone breakthrough phenomenon and may lead to renal protection in patients with chronic kidney disease. Sato and colleagues 13,28 demonstrated that add-on therapy of spironolactone to ARB treatment reduced urinary protein in patients with diabetes who experienced the aldosterone breakthrough phenomenon.…”
Section: Ras Inhibitors (Angiotensin-converting Enzyme Inhibitor or Arb)mentioning
confidence: 99%